استيعاب المفردات وتأثيره في مهارة الكلام - Soraiya Mohammad Usman; Safirah Amalia Agustin; Kisno Umbar (Kalimatuna: Journal of Arabic Research, 2022)
Because of a lack of understanding of students' vocabulary, the researcher picked this issue. The goal of this research is to determine the extent to which children can comprehend vocabulary and communicate, as well as the relationship between vocabulary understanding and speaking skills. A descriptive quantitative method as well as a correlational approach were adopted by the researcher. The average score of the students' written and oral test scores was calculated using the arithmetic mean. Product Moment Correlation was utilized to analyze the data. A total of 52 pupils were chosen for this investigation. Written tests, oral tests, direct observation, and interviews were employed by the researchers in this study to collect data. Because there is a relationship between the two, research suggests that teaching vocabulary comprehension and speaking abilities is excellent and successful.